Posterior Dislocation of Subtalar Joint without Associated Fracture: A Case Report and Review of Literature - Sahil Gaba; Arvind Kumar; Vivek Trikha; Saubhik Das; Prabhat Agrawal (Journal of Clinical and Diagnostic Research, 2017)
Posterior subtalar dislocation is an exceedingly rare entity. Clinically, the appearance of the foot can simulate a complex fracture dislocation. It is important to recognize that not all posterior subtalar dislocations are true posterior dislocations. We report a true posterior subtalar dislocation in a 34-year-old female, managed promptly with closed reduction and resulting in an excellent functional outcome. A chronic dislocation or an irreducible dislocation may need open reduction.